Keeping an eye on cost: What can eye tracking tell us about attention to cost information in discrete choice experiments?. (3rd February 2023) - Genie, Mesfin G.; Ryan, Mandy; Krucien, Nicolas
Abstract: Concern has been expressed about including a cost attribute within discrete choice experiments (DCEs) when individuals do not have to pay at the point of consumption. We use eye tracking to investigate attention to cost when valuing publicly financed health care. One‐hundred and four individuals completed a DCE concerned with preferences for UK general practitioner appointments: 51 responded to a DCE with cost included and 53 to the same DCE without cost. Eye‐movements were tracked whilst respondents completed the DCE. We assessed if respondents pay attention to cost. We then compare fixation time (FT) on attributes, eye movement patterns and mental effort across the experimental groups. Results are encouraging for the inclusion of cost in DCEs valuing publicly provided healthcare. Most respondents gave visual attention to the cost attribute most of the time. Average FT on multi‐attribute tasks increased by 44% in the cost DCE, with attention to non‐monetary attributes increasing by 22%. Including cost led to more structured decision‐making and did not increase mental effort. Acceptability of the cost attribute and difficulty of choice tasks were predictors of cost information processing, highlighting the importance of both motivating the cost attribute and considering difficulty of the tasks when developing DCEs.